Performance of TCP/IP over ATM networks - Hassan, Mahbub (Artech House telecommunications library., 2000)
Gain an in-depth understanding of performance issues central to the planning, designing, and efficient operation of TCP/IP over ATM networks with this practical new book. Containing information essential to solving internetworking problems between TCP/IP and ATM networks, this book helps you guarantee quality of service for ATM applications and understand the enhancements required to run TCP over wireless links.